Perbedaan Hasil Tes Darah Rutin Pasien Suspek Covid-19 Terkonfirmasi Positif Dan Negatif Di RSUD Sultan Suriansyah Banjarmasin - Yayuk Kustiningsih; Ida Fitriyani; Erfan Roebiakto; Anny Thuraidah; Nurlailah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The purpose of this study was to determine the differences in routine blood in COVID-19 suspected patients who were confirmed positive and negative who were treated at the Emergency Room of Sultan Suriansyah Hospital Banjarmasin in the period January-June 2022. This study used naso-oropharyngeal swab samples for RT-PCR examination of COVID-19 and hematology analyzer for routine blood tests. This type of research is an analytic survey research with a comparative design. The population of this study were suspected patients admitted to the emergency room with a total sample size of 196 patients who performed RT-PCR tests and performed routine blood tests at the beginning of the treatment period using purposive sampling method. Routine blood results in positive patients mostly obtained leukocytes at normal limits 64.1%, neutrophilia 59.0%, lymphopenia 64.1% increased NLR 66.7% and platelets at normal limits 56.4%. While in negative patients, leukocytes were obtained at normal limits of 46.6%, neutrophilia 61.0%, lymphopenia 61.0% increased NLR 73.7% and platelets at normal limits 64.4.4%. Based on the results of the unpaired T-test statistical test, it is known that there are significant differences between positive and negative patients, namely in the parameters of leukocytes sig. 0.028, neutrophils sig. 0.043 and platelets sig. 0,005. From the results of the unpaired t-test statistical test on routine blood between positive and negative COVID-19 patients, it was found that there were significant differences in the parameters of leukocytes, neutrophils and platelets, while those that were not different were the parameters of lymphocytes and NLR.